Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3390/ijms20020295
|View full text |Cite
|
Sign up to set email alerts
|

Potential Interplay of the Gatipotuzumab Epitope TA-MUC1 and Estrogen Receptors in Ovarian Cancer

Abstract: Anti-tumor efficacy of Gatipotuzumab, a therapeutic antibody targeting Tumor-Associated Mucin-1 (TA-MUC1), in relapsed ovarian cancer (OC) appeared to be rather heterogeneous. Whether adding a second anti-neoplastic drug may augment response towards Gatipotuzumab, has not been elucidated so far. Since it is known that anti-MUC1 antibodies may alter estrogen receptor activity in breast cancer, this potential interplay was investigated in OC. The correlation between TA-MUC1, estrogen receptors (ERs) and another … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
2
4
0
Order By: Relevance
“…Because the exclusive expression of the FSHR has already been described by our group as a negative prognosticator in ovarian cancer cases, our finding about enhanced expression of both FSHR and THRα in the nucleus might lead to new treatment strategies for this type of cancer (Lenhard et al 2011). This assumption might also apply for the antibody Gatipotuzumab and its TA-MUC1 epitope (Heublein et al 2019), which showed an inverse correlation to THRα1 and -2 expression either in the nucleus or in the cytoplasm, respectively. In addition, T4 has been shown to promote ovarian cancer cell proliferation via integrin αvβ3.…”
Section: Discussionsupporting
confidence: 59%
“…Because the exclusive expression of the FSHR has already been described by our group as a negative prognosticator in ovarian cancer cases, our finding about enhanced expression of both FSHR and THRα in the nucleus might lead to new treatment strategies for this type of cancer (Lenhard et al 2011). This assumption might also apply for the antibody Gatipotuzumab and its TA-MUC1 epitope (Heublein et al 2019), which showed an inverse correlation to THRα1 and -2 expression either in the nucleus or in the cytoplasm, respectively. In addition, T4 has been shown to promote ovarian cancer cell proliferation via integrin αvβ3.…”
Section: Discussionsupporting
confidence: 59%
“…Because the exclusive expression of the FSHR has already been described by our group as a negative prognosticator in ovarian cancer cases, our finding about enhanced expression of both FSHR and THRa in the nucleus might lead to new treatment strategies for this type of cancer [24]. This assumption might also apply for the antibody Gatipotuzumab and its TA-MUC1 epitope [45], which showed an inverse correlation to THRa1 and -2 expression either in the nucleus or in the cytoplasm, respectively.…”
Section: Discussionsupporting
confidence: 58%
“…Furthermore, membrane TAAR1 expression correlated with Muc-115D8 (Spearman rho: 0.226, p = 0.013), VU3C6 (Spearman rho: 0.180, p = 0.044) and negatively with Glycodelin A (Spearman rho: −0.223, p = 0.012) as shown in Table S1. Muc-115D8 and VU3C6 are, similarly to HMFG1, VU4H5, and TA-MUC1, Mucin-1 (MUC1) epitopes generated by various glyco-modifications of MUC1 during the process of malignant transformation [29]. MUC1 is a high molecular weight transmembrane glycoprotein expressed at the luminal membrane of many types of physiological epithelial cells [30].…”
Section: Correlations Of Taar1 and Other Variablesmentioning
confidence: 99%